Pengaruh Ukuran Perusahaan, Pertumbuhan Penjualan, dan Leverage terhadap Financial Distress pada Perusahaan yang Terdaftar di Jakarta Islamic Index Periode 2018-2023 - Mulyaningsih, Herni (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
This study aims to identify and analyze the effect of firm size, sales growth, and leverage on financial distress in companies listed on the Jakarta Islamic Index for the 2018–2023 period. The research sample was obtained using a purposive sampling method, determined based on specific criteria and considerations. The sample consisted of 6 companies listed on the Jakarta Islamic Index during the 2018–2023 period. The method used was multiple linear regression with secondary data and the assistance of the Eviews 12 application. The results of the partial test (t-test) analysis show that: (1) firm size has a negative and insignificant effect on financial distress, (2) sales growth has a negative and insignificant effect on financial distress, and (3) leverage has a negative and significant effect on financial distress. In addition, the results of the simultaneous test analysis show that (4) the three variables—firm size, sales growth, and leverage—simultaneously have a significant effect on financial distress.